Emergency nurse’s perceptions of hospital facility support and disaster preparedness - Dewa Gede Sanjaya Putra; Kuswantoro Rusca Putra; Noorhamdani AS (Intelektual Pustaka Media Utama, 2020)
Disasters cause material losses, morbidity, and deaths. Support for the role of hospitals and health workers, especially nurses, is needed to reduce the number of victims in each disaster. Using a cross-sectional survey design, this study aims to analyze the relationship between nurse’s perceptions of hospital facility support and disaster preparedness. One hundred sixty seven respondents were selected using proportional random sampling. Disaster preparedness evaluation tool (DPET) was used to assess the participants’ readiness, and the Health Sector Self-Assessment Tool for Disaster Risk Reduction was used to assess nurse’s perceptions of hospital facility support. The final results of the analysis using the Spearman Rank test showed a significant correlation between hospital infrastructure support and emergency nurse’s preparedness in disaster preparedness with a p-value (0.00). The higher the nurse’s perceptions of hospital facility support, the higher their preparedness in disaster management is. Strengthening guidelines of disaster planning in hospitals, especially regarding the ability of hospitals to overcome the impacts of disasters, will provide optimal support for emergency nurses during a disaster crisis.